2019
DOI: 10.5267/j.msl.2019.5.028
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of capital structure decisions among publicly listed Islamic banks

Abstract: This research aims to examine bank specific, market and regulatory determinants of leverage and capital structure based on a panel data of publicly listed Islamic banks in 12 countries over the period 2008-2017. Apart from testing standard corporate finance parameters using both OLS and M-Estimators, this study adds several idiosyncratic and regulatory environment related determinants of leverage unique to Islamic banks. The significance of potential determinants is tested for market and book leverage as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The positive impact is consistent with the data of static trade-off theory, which states that large banks prefer to finance their assets with debt because they have a large ability to invest their money with a low degree of risk, and they have a large ability to provide low-cost banking services. This result is consistent with Guizani (2021), Khan et al (2021), Bukair (2019), Khokher & Alhabshi (2019), and Sheikh & Qureshi (2017).…”
Section: Regression Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The positive impact is consistent with the data of static trade-off theory, which states that large banks prefer to finance their assets with debt because they have a large ability to invest their money with a low degree of risk, and they have a large ability to provide low-cost banking services. This result is consistent with Guizani (2021), Khan et al (2021), Bukair (2019), Khokher & Alhabshi (2019), and Sheikh & Qureshi (2017).…”
Section: Regression Resultssupporting
confidence: 88%
“…Some studies suggested Non-Debt Tax Shield (NDTS) as a factor affecting the capital structure. Guizani (2021) and Khokher and Alhabshi (2019) found a positive impact of a Non-Debt Tax Shield on the capital structure. In contrast, Deesomsak et al (2004) and Thabet et al (2017) found a negative impact of a Non-Debt Tax Shield on the capital structure in Islamic banks.…”
Section: Empirical Studies On Determinants Of Capital Structurementioning
confidence: 98%
See 2 more Smart Citations
“…To mobilize funds, IBs use financing instruments including shareholders' equity and investment accounts that differ from those used by CBs. Moreover, IBs are considered to have distinct operational characteristics, risk profiles and balance sheet structures that have implications for the decision parameters of their managers (Khokher and Alhabshi, 2019). Besides, IBs are often constrained by multiple banking regulatory standards.…”
Section: Introductionmentioning
confidence: 99%